1988
DOI: 10.1021/jm00398a009
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric effects of homologs of disoxaril on the inhibitory activity against human rhinovirus-14

Abstract: X-ray crystallography studies of racemic 5-[7-[4-(4,5-dihydro-4-methyl-2-oxazolyl)phenoxy]heptyl]- 3-methylisoxazole bound to human rhinovirus-14 (HRV-14) indicate selective binding of the S isomer. This result correlates well with the 10-fold greater activity of the S isomer as compared to the R isomer. The enantiomeric effect on activity is explained by a hydrophobic interaction of the methyl group in the case of 2a, with a pocket formed by Leu106 and Ser107. The 4-ethyl, 4-propyl, and 4-butyloxazolinyl homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A canyon or depression (about 2.5-nm deep) encircles each of the virion's pentamer vertices (22). A number of structurally related antipicornaviral compounds, which were synthesized at the Sterling Research Group, Rensselaer, N.Y. (7,8), have been instrumental as an aid in exploring the structure of rhinoviruses relative to the early events in the viral replication processes. One of these compounds, disoxaril, was reported to interact directly with the virion capsid and stabilize the capsid conformation against thermal inactivation (10).…”
mentioning
confidence: 99%
“…A canyon or depression (about 2.5-nm deep) encircles each of the virion's pentamer vertices (22). A number of structurally related antipicornaviral compounds, which were synthesized at the Sterling Research Group, Rensselaer, N.Y. (7,8), have been instrumental as an aid in exploring the structure of rhinoviruses relative to the early events in the viral replication processes. One of these compounds, disoxaril, was reported to interact directly with the virion capsid and stabilize the capsid conformation against thermal inactivation (10).…”
mentioning
confidence: 99%
“…As with homologues of disoxaril (Diana et al, 1987(Diana et al, , 1988, the introduction of alkyl groups at position 4 of the oxazoline ring improves both the anti-HRV-14 and anti-HRV-2 activity of derivatives 5 (which have six methylene groups in the ketomethylene chain connecting the thiophene ring to the 4-(oxazolin-2-yl)phenoxy moiety) while not influencing the activity of counterparts with four methylene groups (compound 4). As for WIN derivatives, S enantiomers are more active than R enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…1), it has been shown that the introduction of alkyl substituents at position 4 of the oxazoline ring led to derivatives (2) which showed greater activity than 1 against several rhinovirus serotypes (Diana et al, 1988). Among the 4-alkyloxazolines, the S enantiomer of 2a has been shown to be 10 times more effective than disoxaril in inhibiting human rhinovirus-14 .…”
Section: Introductionmentioning
confidence: 99%
“…The plaque reduction assay has been traditionally performed and accepted as the ''gold standard'' in antiviral testing. [137][138][139] However, this test is laborious, time consuming, and the evaluation is subjective. Therefore, it is not suited for the routine antiviral testing.…”
Section: A Experimental Approaches For Anti-hrv Studiesmentioning
confidence: 99%